Red [videorecording (DVD)] - Schwentke, Robert, 1968-; Willis, Bruce, 1955-; Mirren, Helen; Malkovich, John; Parker, Mary-Louise; Freeman, Morgan; Ellis, Warren; Hamner, Cully (Summit Entertainment, 2011)
Frank is a former black-ops CIA agent living a quiet life alone, until the day a hit squad shows up to kill him. With his identity compromised, Frank reassembles his old team; Joe, Marvin, and Victoria, and sets out to prove that they still have a few tricks up their sleeves. Stand back and watch the bullets fly in this explosive action-comedy.